Field-induced slow magnetic relaxation in two interpenetrated cobalt(ii) metal–organic framework isomers. Issue 32 (5th August 2020) - Wei, Xiao-Qin; Shao, Dong; Xue, Cai-Long; Qu, Xing-Yu; Chai, Jie; Li, Jian-Qing; Du, Yi-En; Chen, Yong-Qiang
Abstract : Two interpenetrated cobalt(ii ) metal–organic framework (MOF) isomers were successfully synthesized and magnetically characterized. These compounds are the first example of MOF isomers showing field-induced single-ion magnet behavior. Abstract : Field-induced slow magnetic relaxation was observed in two interpenetrated cobalt(ii ) metal–organic framework (MOF) isomers constructed from a dual-functional ligand 1 H -benzimidazole-5-carboxylic acid, which represent the first example of MOF isomers showing field-induced single-ion magnet behavior.